2016
DOI: 10.1016/j.phrs.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

PPARα in lysosomal biogenesis: A perspective

Abstract: Lysosomes are membrane-bound vesicles containing hydrolytic enzymes, ubiquitously present in all eukaryotic cells. Classically considered to be central to the cellular waste management machinery, recent studies revealed the role of lysosomes in a wide array of cellular processes like, degradation, cellular development, programmed cell death, secretion, plasma membrane repair, nutritional responses, and lipid metabolism. We recently studied the regulation of TFEB, considered to be the master regulator of lysoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…Stimulation of cytosolic PPARα by aspirin binding results in the dimerization of PPARα and retinoid X receptor gamma (RXRγ) and subsequent translocation to the nucleus [ 27 , 28 ]. Once in the nucleus, the dimer associates with PPARG coactivator 1 alpha (PGC1α) and binds to the promoter region of the transcription factor EB (TFEB) gene [ 28 , 29 ]. Production of unphosphorylated TFEB, a master regulator of lysosomal biogenesis, promotes both a positive feedback loop that leads to production of more TFEB as well as promotes the expression of essential lysosomal components [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of cytosolic PPARα by aspirin binding results in the dimerization of PPARα and retinoid X receptor gamma (RXRγ) and subsequent translocation to the nucleus [ 27 , 28 ]. Once in the nucleus, the dimer associates with PPARG coactivator 1 alpha (PGC1α) and binds to the promoter region of the transcription factor EB (TFEB) gene [ 28 , 29 ]. Production of unphosphorylated TFEB, a master regulator of lysosomal biogenesis, promotes both a positive feedback loop that leads to production of more TFEB as well as promotes the expression of essential lysosomal components [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once in the nucleus, the dimer associates with PPARG coactivator 1 alpha (PGC1α) and binds to the promoter region of the transcription factor EB (TFEB) gene [ 28 , 29 ]. Production of unphosphorylated TFEB, a master regulator of lysosomal biogenesis, promotes both a positive feedback loop that leads to production of more TFEB as well as promotes the expression of essential lysosomal components [ 28 , 29 , 30 ]. The increase in lysosome production and activity may increase the clearing of accumulated Tau proteins and decrease the entanglement of neurofibrillary fibers, a hallmark of AD, through the autophagy-lysosome pathway (ALP) [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…TFEB is the master regulator of lysosomal 249 biogenesis and, consequently, of LAL expression. Recently, peroxisome proliferator 250 responsive elements were identified in the promoter region of TFEB and it has been shown 251 that PPARα, together with PPAR gamma coactivator 1α and retinoid X receptors, can 252 promote the transcriptional activation of TFEB [23]. In addition, PPARα agonists could directly 253 promote LAL activity through their modulation of intracellular lipid metabolism.…”
Section: Discussion 205mentioning
confidence: 99%
“…TFEB is the master regulator of lysosomal biogenesis and, consequently, of LAL expression. Recently, peroxisome proliferator responsive elements were identified in the promoter region of TFEB and it has been shown that PPARα, together with PPAR gamma coactivator 1α and retinoid X receptors, can promote the transcriptional activation of TFEB [23]. In addition, PPARα agonists could directly promote LAL activity through their modulation of intracellular lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%